Catheter Ablation of Atrial Fibrillation in Patients With Functional Mitral Regurgitation and Left Ventricular Systolic Dysfunction - Wu, Jin-Tao; Zaman, Junaid A. B.; Yakupoglu, H. Yakup; Vennela, Boyalla; Emily, Cantor; Nabeela, Karim; Jarman, Julian; Haldar, Shouvik; Jones, David Gareth; Wajid, Hussain; Shi, Rui; Chen, Zhong; et al. (Frontiers in Cardiovascular Medicine, 2020)
Background: The efficacy of catheter ablation for atrial fibrillation (AF) in patients with functional mitral regurgitation (MR) and left ventricular (LV) systolic dysfunction (LVSD) is not known. The aim of the study is to determine the efficacy of catheter ablation for AF in patients with functional MR and LVSD, and to validate its effects on the severity of MR and cardiac reverse remodeling. Methods: We performed a retrospective study of 54 patients with functional MR who underwent AF ablation, including 21 (38.9%) with LVSD and 33 (61.1%) with normal LV systolic function (LVF). The primary outcomes evaluated were freedom from recurrent atrial tachyarrhythmia (ATa), severity of MR, and left atrial (LA) and LV remodeling. Results: During a mean follow-up of 20.7±16.8 months, freedom from recurrent ATa was not significantly different between patients with LVSD and those with normal LVF after the first ablation (P=0.301) and after multiple ablations (P=0.728). Multivariable predictors of recurrent ATa were AF duration (hazard ratio [HR] 1.12, 95% confidence interval [CI] 1.01-1.25; P=0.039), previous stroke (HR 5.28, 95% CI 1.46-19.14; P=0.011), and estimated glomerular filtration rate (HR 0.97, 95% CI 0.95-0.99; P=0.012). Compared with baseline, there was a significant reduction in severity of MR (P=0.007), LA size (P<0.001) and LV end-systolic dimension (P=0.008), and improvement in the LV ejection fraction (P=0.001) after restoring sinus rhythm in patients with LVSD. Conclusion: Catheter ablation is a valid option for the treatment of AF in patients with functional MR and LVSD, even though multiple procedures may be required.